2020
DOI: 10.1080/09640568.2020.1766427
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability materiality matrices in doubt: may prioritizations of aspects overestimate environmental performance?

Abstract: This study builds on the research gap that arises from the consistency analysis of GRImateriality approach with other prioritization approaches. The main objective is to explore to what extent corporate environmental performance is consistent using two different prioritization approaches. This study employs a novel quantitative approach to assess environmental performance through the prioritization of environmental aspects by using companies' materiality analysis and independent expert knowledge. The empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 93 publications
(111 reference statements)
1
12
0
1
Order By: Relevance
“…These pressures over materiality analysis refer to greenwashing behaviour (Zharfpeykan, 2021), rhetorical or symbolic representation of sustainability (Unerman and Zappettini, 2014), ceremonial reporting processes (Haji and Anifowose, 2016), moral fictionalism (Boiral et al , 2021), the consideration of sustainability through a financial materiality lens (Cerbone and Maroun, 2020) and different methodologies for materiality applications (Eccles et al , 2020). For instance, Ferrero-Ferrero et al (2021) found that companies with higher level of environmental performance could use materiality analysis to further embellish positive performance or for greenwashing purposes. Impression management strategy –that is, the symbolic use of disclosure to advance the corporate image (Chen et al , 2014) – and the mismanagement of sustainability – that is, a firm’s incorrect handling of sustainability issues in terms of the discrimination between material and immaterial sustainability topics – lead to greater performance levels on immaterial sustainability issues than on material ones (Maniora, 2018, p. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These pressures over materiality analysis refer to greenwashing behaviour (Zharfpeykan, 2021), rhetorical or symbolic representation of sustainability (Unerman and Zappettini, 2014), ceremonial reporting processes (Haji and Anifowose, 2016), moral fictionalism (Boiral et al , 2021), the consideration of sustainability through a financial materiality lens (Cerbone and Maroun, 2020) and different methodologies for materiality applications (Eccles et al , 2020). For instance, Ferrero-Ferrero et al (2021) found that companies with higher level of environmental performance could use materiality analysis to further embellish positive performance or for greenwashing purposes. Impression management strategy –that is, the symbolic use of disclosure to advance the corporate image (Chen et al , 2014) – and the mismanagement of sustainability – that is, a firm’s incorrect handling of sustainability issues in terms of the discrimination between material and immaterial sustainability topics – lead to greater performance levels on immaterial sustainability issues than on material ones (Maniora, 2018, p. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The major risk is that corporate managers can disclose their environmental and social impacts as a mechanism for legitimising organisational actions (Murphy and McGrath, 2013; Sepúlveda-Alzate et al , 2021). To mitigate or eventually overcome this issue, the inclusion of sustainability issues that are relevant for companies and stakeholders is fundamental to sustainability accounting and reporting (Ferrero-Ferrero et al , 2021). This process, also known as materiality analysis, helps companies identify, assess and prioritise corporate sustainability practices that impact both the company and its stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a report should include concerned stakeholders who are either greatly influenced by the company or who themselves influence the successful implementation of the company objectives and address the related topics [103]. The materiality matrix is the most utilized method to define materiality issues [32,104], and the most important and complex among other standards [105] at the global level [106]. The concept of materiality is understood as a reporting threshold [107,108], and is the main guideline to reducing the issue of low credibility [109].…”
Section: Sustainability Reporting and Materiality Matrixmentioning
confidence: 99%
“…For instance, one of the research issues concerning the definition of materiality is that there is no final definition of materiality in inferential sustainability research or at an institutional level [104]. In addition, Ferrero-Ferrero et al studied evidence showing that materiality assessment still faces many constraints in sustainability reports [32]. The materiality analysis process aims to identify and prioritize pertinent aspects and issues of the company, the result of which is a materiality matrix that designates the company and stakeholder views on the importance of related issues [115].…”
Section: Sustainability Reporting and Materiality Matrixmentioning
confidence: 99%
See 1 more Smart Citation